Educational policy and school constructions in the district of La Victoria (Peru) during the government of Odría, 1948-1956 - Martinez Mendoza, Juan Marcos (Historia y Memoria de la Educación, 2022)
The government of Manuel A. Odría (1948-1956) is remembered in Peru as one of the governments that best addressed the problem of the shortage of schools during the 20th century; however, in the construction of an overview of his educational work, certain issues have been omitted, such as the neglect of the regime towards primary schools, the effects that the first intense migrations—from the countryside to the city—had on the schools in the capital and the critical final years that diminished the government’s educational work. This article seeks to give a general overview of Odría’s educational policy, with emphasis on school buildings, for which the capital district of La Victoria has been taken as a case study. Through the study of official documents and information extracted from the press, we show that the government had a preference for secondary and technical education that ended up affecting the construction of schools; and that after 1953 Odría’s educational work decreased due to political, economic and social factors.